(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Regardless of fact that earth’s form cannot alteration, world is fast becoming a global community as world’s populace consumes more energy on a frequent basis. Energy & related services have become progressively crucial for human economic & social development, well-being, & healthcare. Turning to renewable to address climate alteration is a fantastic concept, but it should be sustained with intention of meeting energy capacity of upcoming generations. Research examined benefits of renewable sources of energy, like security of energy, access of energy, socio - economical development, mitigating climate alteration, & reduced health & ecological impacts. Notwithst&ing se benefits, re are still barriers to renewable energy sources’ long-term sustainability in terms of mitigating climate alteration. Among se difficulties include market distortions, deficiency of information, procurement of raw resources for foreseeable renewable resource deployment, & everyday carbon impact. Research suggests policies & activities that, if followed, would assistance in attaining objective of renewable energy, lowering emanations, dealing with climate alteration, & delivering sterile atmosphere & clean energy to all present & upcoming generations.